Effects of captopril and a combination of hydralazine and isosorbide dinitrate on myocardial sympathetic tone in patients with severe congestive heart failure. Issue 2 (August 1986) - Daly, P; Rouleau, J L; Cousineau, D; Burgess, J H; Chatterjee, K
Abstract : Changes in circulating catecholamines and transmyocardial catecholamine balance associated with improved left ventricular function were studied in patients with chronic heart failure after treatment with captopril (10 patients) and hydralazine in combination with isosorbide dinitrate (eight patients). Cardiac performance improved in response to both captopril and hydralazine-nitrate treatment. The systemic haemodynamic effects were also qualitatively similar, but the hydralazine-nitrate combination caused a greater increase in cardiac index and heart rate. Captopril did not change arterial adrenaline concentrations (0.63 to 0.60 nmol/l), arterial noradrenaline (4.2 to 3.9 nmol/l), or net transmyocardial noradrenaline release (390 to 317 pmol/min), while hydralazine-nitrate increased arterial adrenaline (0.91 to 1.47 nmol/l) and transmyocardial noradrenaline release (225 to 554 pmol/min). Although both captopril and hydralazine-nitrate treatment improve left ventricular performance in patients with chronic heart failure, hydralazine-nitrate enhances cardiac sympathetic tone and captopril does not. The clinical relevance of these findings, however, is not known.